(untitled) (Revista Cientifica Ingenio Magno, 2019)
Muscles contribute to the movement, in addition to providing protection to the bones, veins, arte-ries and organs, besides they shape the body. In this article, we describe a non-invasive method to evaluate the functional status of muscles based on muscle temperature, used to track the performance of athletes. The study was developed with different groups of subjects, each with a different sport activity (runners and physicist-constructivists) and, in turn, often with different training frequency (intense and moderate), to which a non-invasive muscle test was applied; with the statistical analysis of the obtained data it was possible to characterize, in a differential way, the muscular behavior in terms of heat released, corresponding to each experimental group.